Study on real-time detection method for electron beam selective melting process. (November 2020) - Wang, Jiaming; Yin, Bohua; Liu, Junbiao; Wang, Pengfei; Sun, Botong; Han, Li
Abstract: In order to solve the problem of lack of effective and real-time monitoring evaluation method for electron beam selective melting (EBSM) processing, a technique of acquiring real-time secondary electron (SE) imaging through layer-by-layer scanning is presented, which could monitor the defects of components. Basic design scheme, including the Electron beam scanning system, signal processing and imaging system, is introduced in this paper. Capability of generating digital image and choosing different monitoring area for the real-time monitoring system has been verified by series of experiments. Results suggest that the maximum resolution of the prototype has reached 0.3mm.